2013
DOI: 10.2174/1389557511313120007
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on SAR of Curcumin

Abstract: Curcumin, a natural diaryl heptanoid continues to be used as an alternative medicinal agent in many parts of South East Asia for treatment of many ailments. It can be usually obtained from substituted aryl aldehydes and acetylacetone and this route enables synthesis of a diverse set of curcumin analogues. Numerous analogues have been synthesized and tested by several researchers to investigate their activity against known biological targets and to improve upon the pharmacological and ADME profile by modifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Whereas potential health benefits of parent curcumin and its anticancer, anti-inflammatory, antioxidant, and anti-mutagenic effects have been extensively studied, [1][2][3][4][5] its complex signaling pathways and biological profile, coupled to poor pharmacokinetic properties have been major obstacles in developing a CUR-based anti-cancer drug, despite much effort to devise delivery methods by nanotechnology formulation or encapsula-tion into liposomes, or by inclusion into water soluble host molecules such as β-cyclodextrin. [6][7][8] Much work has been devoted to improving solubility, metabolic stability, lipophilicity, and other properties through synthesis of analogs, and these developments have been summarized in recent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas potential health benefits of parent curcumin and its anticancer, anti-inflammatory, antioxidant, and anti-mutagenic effects have been extensively studied, [1][2][3][4][5] its complex signaling pathways and biological profile, coupled to poor pharmacokinetic properties have been major obstacles in developing a CUR-based anti-cancer drug, despite much effort to devise delivery methods by nanotechnology formulation or encapsula-tion into liposomes, or by inclusion into water soluble host molecules such as β-cyclodextrin. [6][7][8] Much work has been devoted to improving solubility, metabolic stability, lipophilicity, and other properties through synthesis of analogs, and these developments have been summarized in recent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous analogs have been synthesized and are being tested against known biological targets to improve upon the pharmacological, absorption, distribution, metabolism and secretion profile by modifying substitutions on its aromatic rings, the β-diketone moiety, and the two flanking double bonds that are conjugated to the β-diketone moiety. This has led the way for researchers to further study the structure-activity relationship of curcumin in medicinal chemistry [209, 210]. Interestingly, Pisano et al [211] recently showed that a new curcumin analog alpha,beta-unsaturated ketone D6 [(3E,3'E)-4,4'-(5,5',6,6'-tetramethoxy-[1,1'-biphenyl]-3,3'-diyl)bis(but-3-en-2-one)] (Fig.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
“…Studies performed in vitro pointed out that this natural compound appears as an interesting epigenetic modulator [27,28] that possesses anti-oxidant [13,29,30], anti-inflammatory [31,32,33], anti-proliferative [34,35] and anti-angiogenic [36,37] properties in the micromolar concentration range in several cancer cell types. Curcumin’s structure-activity relationship was established by the comparison of the bioactivity of curcumin and its naturally occurring analogs, including its demethoxy derivatives (demethoxycurcumin and bisdemethoxycurcumin) and its active hydrogenated metabolites (tetrahydrocurcumin, hexahydrocurcumin and octahydrocurcumin) (Figure 1) [38,39,40], but also by the synthesis of curcumin analogs [41,42,43]. It became clear that the high anti-inflammatory and anti-tumor potentials of curcuminoids are related to their low level of hydrogenation and high level of methoxylation, but also to the high level of unsaturation of the diketone moiety [44].…”
Section: Curcuminmentioning
confidence: 99%
“…The structure activity relationship (SAR) of curcumin was established based on the design and the analysis of the SAR and anticancer effect of curcumin-derived molecules [38,41,42,43,52]. Structural modifications of the curcumin scaffold were also elaborated in order to improve the low bioavailability of curcumin by increasing its hydrophilicity, by facilitating its transmembrane passage and increasing the delay of metabolism.…”
Section: Strategies To Enhance Curcumin Bioavailabilitymentioning
confidence: 99%